THE EFFECT OF WORKLOAD AND WORK STRESS ON EMPLOYEE SPIRIT AT THE REGIONAL TAX AND LEVEL MANAGEMENT AGENCY OF UPT SAMSAT MEDAN SELATAN - Yuni Andri Ekawati (SEAN Institute, 2022)
This study aims to determine whether there is an effect of workload and work stress on the morale of employees at the Regional Tax and Retribution Management Agency of UPT SAMSAT South Medan and how big the effect is. The method used in this study is a quantitative method with several tests, namely reliability analysis , classical assumption deviation test and linear regression . Based on the results of the primary data regression which was processed using SPSS 18, the following multiple linear regression equation was obtained: Y = 20,113 + 0,069 X 1 + 0,441 X 2. Partially, the workload variable (X 1 ) has no significant effect on the morale of the employees of the Regional Tax and Levy Management Agency of UPT SAMSAT South Medan. This means that the hypothesis in this study is not accepted, as evidenced by the value of t count < t table (0.581 < 1.668). While the work stress variable (X 2 ) has a significant effect on the morale of the employees of the Regional Tax and Levy Management Agency of UPT SAMSAT South Medan. This means that the hypothesis in this study is accepted, as evidenced by the value of t count > t table (4.358 > 1.691). Simultaneously, the workload variable (X1 ) and work stress (X2 ) have a positive and significant effect on the morale of the employees of the Regional Tax and Levy Management Agency UPT SAMSAT South Medan. This means that the hypothesis in this study is accepted, as evidenced by the calculated F value > F table (12,010 > 3,13 ) . Workload variables (X1 ) and work stress (X2 ) were able to contribute to the influence of the employee morale variable by 26.1% while the remaining 73.9% was influenced by other variables not examined in this study such as work discipline variables and job satisfaction. From the conclusions above, the authors suggest that employees should do refreshing so that the workload and work stress are not felt too heavy. It is better if the head of service does not give a workload that is too heavy so that employees do not feel stressed when working. Employees should remain enthusiastic in working even though they have to carry a heavy workload.